Imunogenic Protein of Salivary Gland from Anopheles sundaicus - Armiyanti, Yunita; Nuryady, Moh Mirza; Utomo, Sugeng Setyo; Sardjono, Teguh Wahju; Fitri, Loeki Enggar; Senjarini, Kartika (UNEJ e-Proceeding, 2014)
Malaria is still a major problem for developing countries, including Indonesia. One approach to overcome this disease is prevention by vaccination. However, there is still no effective malaria vaccine that is applicable. The ideal malaria vaccine is a combination vaccine that can prevent the pre-erythrocytic cycle, the erythrocytic cycle and transmission process. Salivary vector-based vaccine has the potential to be developed as a malaria vaccine because it can prevent transmission process and also decrease the morbidity of the disease. Saliva from Anopheles contains vasomodulator and immunomodulatory components, that are required in the blood feeding process, but in the same time it could enhance the transmission of the malaria parasite. If the component in the salivary vector can increase pathogen infection, then vaccinating the host with its anti-substances can control the transmission of pathogens (Transmision Blocking Vaccine). Anopheles sundaicus is an important vector of malaria in coastal areas of Java, Bali, Sumatra, Kalimantan and West Nusa Tenggara islands. Repeated exposures of Salivary Gland Extract (SGE) from this vector have been proven to be able to decrease parasitemic rates in mouse model for malaria in our study. The objective of this research is to determine and localize the immunogenic protein from SGE of An. sundaicus as the first step for the characterization of its immunomodulatory component. Mosquito salivary gland protein profile of An.sundaicus was determine by SDS-PAGE. Determination of salivary glands immunogenic proteins was conducted by Western Blotting with IgG from people living from endemic area as primary antibody. Out of 15 bands appeared in SDS PAGE ranging from 24 kD to 138 kD, only two protein bands withÂ  molecular weights of 68 and 37 kDa were the most immunogenic. Those immunogenic proteins were consistent recognized by pooled serum of people as well as by individual response. Keywords: malaria, saliva, vector, immunogenic protein, vaccine